5S´s una herramienta de calidad para la mejora del desempeño operativo: Un estudio en las empresas de la cadena automotriz de Nuevo León (5S as a tool for improving operational performance: A study in the automotive supply chain companies in Nuevo Leon) - Rodarte, Armandina; Monica, Blanco (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. This study, presented the findings in medium and large companies who have implemented de Japanese 5S´s methodology and the effects caused in the operational performance variables: ecological waste management, secure facilities in the company, image with the internal customer, increased quality standards, increased productivity, fewer accidents, external customer image and reduced the amount of rework.